'D' excision for sacrococcygeal pilonidal sinus disease. - Mann, C V (1987)
A new procedure is described for treating pilonidal sinus by an excision and primary suture technique, and the results reported in 30 consecutive patients so treated--28 with chronic sinuses and 2 with an acute abscess. Seventeen patients (Group 1) had had no previous surgery, while 13 (Group 2) had had multiple previous operations. A total of 24 patients (80%) healed after the operation, their mean hospital stay being 16 days. In Group 1 the success rate was 88% with a mean hospital stay of 15 days; in Group 2 the comparable figures were 69% and 17 days. After additional procedures (usually curettage) all patients healed.